TEKNIK PEMERIKSAAN RADIOGRAFI COLON IN LOOP DENGAN KLINIS HEMOROID GRADE IV SUSPECT POLIP RECTI DI INSTALASI RADIOLOGI RS ISLAM JAKARTA CEMPAKA PUTIH - Suci Rahma Oktaria; Anisa Nur Istiqomah; Retno Wati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The colon is an important part of the digestive system that may develop various abnormalities, such as hemorrhoids and polyps. The colon in loop examination for patients with grade IV hemorrhoids and suspected rectal polyps at the Radiology Department of Jakarta Islamic Hospital Cempaka Putih (RSIJCP) differs from the standard theory, particularly regarding patient preparation and radiographic projections. This study aimed to identify the examination procedure, the rationale for patient preparation, and the use of radiographic projections at RSIJCP. A qualitative study with a case study approach was conducted from September 2025 to April 2026. The subjects consisted of three radiographers and one radiologist. Data were collected through observation, interviews, and documentation, then analyzed narratively through data reduction, theory comparison, and conclusion drawing. The results showed that patient preparation involving a 6-hour fasting period and morning bowel evacuation was considered adequate to cleanse the colon and reduce discomfort in patients with grade IV hemorrhoids. The use of Anteroposterior (AP), Lateral, and Right Posterior Oblique (RPO) projections provided sufficient diagnostic information to evaluate abnormalities in the rectum while minimizing radiation exposure. The double-contrast technique enhanced the visualization of lesions suspected as rectal polyps. It can be concluded that the colon in loop examination procedure at RSIJCP is adequate for supporting diagnosis while maintaining patient safety and comfort. The use of bowel preparation without Dulcolax suppositories is recommended to minimize the risk of complications. ABSTRAK Colon merupakan bagian penting sistem pencernaan yang dapat mengalami berbagai kelainan, seperti hemoroid dan polip. Pemeriksaan colon in loop pada kasus hemoroid grade iv suspect polip recti di Instalasi Radiologi RS Islam Jakarta Cempaka Putih (RSIJCP) memiliki perbedaan dengan teori, terutama pada persiapan pasien dan penggunaan proyeksi radiografi. Penelitian ini bertujuan mengetahui prosedur pemeriksaan, alasan pemilihan persiapan pasien, serta penggunaan proyeksi pemeriksaan di RSIJCP. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus pada September 2025–April 2026. Subjek penelitian terdiri atas tiga radiografer dan satu dokter spesialis radiologi. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis secara naratif melalui reduksi data, perbandingan teori, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa persiapan pasien berupa puasa 6 jam dan buang air besar pada pagi hari dinilai memadai untuk membersihkan colon serta mengurangi risiko ketidaknyamanan pada pasien hemoroid grade iv Penggunaan proyeksi Antero Posterior (AP), Lateral, dan Right Posterior Oblique (RPO) memberikan informasi diagnostik yang cukup untuk mengevaluasi kelainan pada area rectum dengan paparan radiasi yang lebih minimal. Teknik double contrast membantu memperjelas visualisasi lesi yang dicurigai sebagai polip recti. Disimpulkan bahwa prosedur pemeriksaan colon in loop di RSIJCP telah memadai untuk mendukung diagnosis serta mempertimbangkan keamanan dan kenyamanan pasien. Disarankan penggunaan persiapan urus-urus tanpa dulcolax suppositoria untuk meminimalkan risiko komplikasi.